The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.aquatox.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic-only arsenic exposure alters skeletal muscle satellite cell function in killifish (Fundulus heteroclitus)

Abstract: Arsenic is a contaminant found worldwide in drinking water and food. Epidemiological studies have correlated arsenic exposure with reduced weight gain and improper muscular development, while in vitro studies show that arsenic exposure impairs myogenic differentiation. The purpose of this study was to use Fundulus heteroclitus or killifish as a model organism to determine if embryonic-only arsenic exposure permanently reduces the number or function of muscle satellite cells. Killifish embryos were exposed to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The high expression of the MyoD gene may be involved in the regulation of the normal structure and motor function of the tail handle muscle. Desmin is an intermediate lament protein closely related to muscle tissue development and structural stability (Szymkowicz et al, 2018). The high expression of Desmin in zebra sh myocardium, dorsal muscle, and tail handle muscle may be involved in the tissue structure.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of the MyoD gene may be involved in the regulation of the normal structure and motor function of the tail handle muscle. Desmin is an intermediate lament protein closely related to muscle tissue development and structural stability (Szymkowicz et al, 2018). The high expression of Desmin in zebra sh myocardium, dorsal muscle, and tail handle muscle may be involved in the tissue structure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that arsenic exposure induced skeletal muscle injury via generating more reactive oxygen species as well as restraining mitophagy and mitochondrial function in mice and duck 10–12 . Moreover, in vivo studies, arsenic exposure reduced the function of muscle satellite cells and thus impaired myogenic differentiation, which maybe mediated by NF‐κB 13,14 . In vitro studies have also confirmed that inorganic arsenic induced cytotoxicity to skeletal muscle cells by inhibiting myogenic differentiation and muscle regeneration and inducing C 2 C 12 myotube atrophy 15 .…”
Section: Introductionmentioning
confidence: 96%
“…[10][11][12] Moreover, in vivo studies, arsenic exposure reduced the function of muscle satellite cells and thus impaired myogenic differentiation, which maybe mediated by NF-κB. 13,14 In vitro studies have also confirmed that inorganic arsenic induced cytotoxicity to skeletal muscle cells by inhibiting myogenic differentiation and muscle regeneration and inducing C 2 C 12 myotube atrophy. 15 However, the mechanism of skeletal muscle metabolic dysfunction in arsenic-induced skeletal muscle atrophy remains largely unknown.…”
mentioning
confidence: 96%